2012
DOI: 10.3727/096368912x637505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Hepatocyte Transplantation in Four Pediatric Patients with Inherited Metabolic Diseases

Abstract: Hepatocyte transplantation (HT) has become an effective therapy for patients with metabolic inborn errors. We report the clinical outcome of four children with metabolic inborn errors that underwent HT, describing the cell infusion protocol and the metabolic outcome of transplanted patients. Cryopreserved hepatocytes were used as this allows scheduling of treatments. Functional competence (viability, cell attachment, major cytochrome P450 and UDP-glucuronosyltransferase 1A1 activities, and urea synthesis) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 53 publications
(211 reference statements)
1
46
0
4
Order By: Relevance
“…Pilot studies of hepatocyte transplantation have demonstrated persistence of donor cells, although the long-term efficacy of this approach remains to be demonstrated 186,187 Efficacy from liver-targeted gene therapy in GSD Ia might be expected, given the experience with human patients after liver transplantation. Adeno-associated virus (AAV) vectors containing a human G6Pase regulatory cassette/promoter have proven to be efficacious in animal models of GSD Ia, and these vectors contain sequence elements that regulate G6Pase expression appropriately.…”
Section: Box 10 Genetic Counseling/prenatal Diagnosis/screening Recommentioning
confidence: 99%
“…Pilot studies of hepatocyte transplantation have demonstrated persistence of donor cells, although the long-term efficacy of this approach remains to be demonstrated 186,187 Efficacy from liver-targeted gene therapy in GSD Ia might be expected, given the experience with human patients after liver transplantation. Adeno-associated virus (AAV) vectors containing a human G6Pase regulatory cassette/promoter have proven to be efficacious in animal models of GSD Ia, and these vectors contain sequence elements that regulate G6Pase expression appropriately.…”
Section: Box 10 Genetic Counseling/prenatal Diagnosis/screening Recommentioning
confidence: 99%
“…Despite clinical improvements in patients, significant problems have arisen because of inefficient engraftment, death or ectopic distribution of cells that did not engraft in the target tissue, emboli formation, immunological rejection, and transient effects of transplanted cells [34][35][36]. A number of preconditioning regimens including irradiation or chemicals have been tried but discontinued for various reasons such as senescence, radiation hazards, or an increased risk of cancer [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were assessed for viability, attachment to collagen-coated plates, drug-metabolizing activities (CYP3A4, CYP2C9, CYP2E1, CYP2A6 and CYP1A2), UDP-glucuronosyltransferase 1A1 and urea formation from ammonia as previously described [18,21]. …”
Section: Methodsmentioning
confidence: 99%
“…Human hepatocytes were prepared from livers rejected for LT and freshly isolated hepatocytes were cryopreserved in University of Wisconsin solution containing 10% dimethyl sulfoxide as described previously in detail [18]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation